Plant Biomass and Productivity Estimates for Central Himalayan Mixed Banj Oak (quercus leucotrichophora A.Camus)-chir Pine (Pinus roxburghii Sarg.) Forest - Rana, B. S.; Singh, R. P. (Indian Forester, 1990)
Plant biomass and net primary production of a mixed banj oak (Quercus leucotrichophora A.Camus)-chir pine (Pinus roxburghii Sarg) forest are described. Of the total forest biomass (4328 t ha-1) and net primary production (18.9 t ha-1 yr-l) trees accounted for 98.5% and 84.1% respectively. Present estimates are comparable with the forest communities of highly favourable environment.